Hubungan Caring Perawat dengan Kepuasan Pasien di Ruang Rawat Inap RS Adam Talib Cikunir - Susanto, I Gede Arya; Isnaeni, Isnaeni (Universitas Malahayati, 2025)
ABSTRACT The quality of hospital services is very important because it functions as a benchmark for improving services, thus encouraging patient satisfaction. Patient satisfaction is considered to have been achieved if the needs, desires, and expectations of patients can be met. Good nursing caring behavior can improve the quality of service and have a good impact on the hospital, one of which is the level of patient satisfaction. To determine correlation nurse caring and patient satisfaction in the Inpatient Room of Adam Talib Cikunir Hospital in 2024. This study was conducted with a cross-sectional research design. The population in this study was the number of hospitalized patients as many as 60 patients and the number of samples as many as 53 respondents with a purposive sampling technique. The research instrument used a questionnaire. Data analysis used univariate analysis and bivariate analysis using chi square. The results of the study showed that nurse caring was good as many as 41 (77.4%) and the satisfied category was 42 (79.2%). The results of the chi square test showed that the p value was 0.001, meaning that there was a correlation Nurse Caring and Patient Satisfaction. There is a relationship between nurse caring and patient satisfaction in the Inpatient Room of the Hospital. It is expected that nurses can apply caring behavior so that they can optimize the provision of nursing care, especially for inpatients, in order to increase patient satisfaction. Keywords: Caring, Satisfaction, Nurses. ABSTRAK Kualitas layanan rumah sakit sangat penting karena berfungsi sebagai tolak ukur untuk meningkatkan layanan, sehingga mendorong kepuasan pasien. Kepuasan pasien dinilai sudah tercapai apabila kebutuhan, keinginan, dan harapan pasien dapat dipenuhi. Perilaku caring perawat yang baik dapat meningkatkan mutu pelayanan dan memberikan dampak yang baik untuk rumah sakit salah satunya yaitu tingkat kepuasan pasien. Untuk mengetahuihubungan caring perawat dengan kepuasan pasien di Ruang Rawat Inap RS Adam Talib Cikunir Tahun 2024. Penelitian ini dilakukan dengan desain penelitian cros sectional. Populasi dalam penelitian ini yaitu jumlah pasien yang dirawat inap sebanyak 60 pasien dan jumlah sampel sebanyak 53 responden dengan tehnik pengambilan sampel purposive sampling. Intrumen penelitian menggunakan kuesioner. Analisis data menggunakan analisis univariat dan analisis bivariat menggunakan chi square. Hasil penelitian menunjukan bahwa caring perawat baik sebanyak 41 (77,4%) responden dan sebagian besar puas sebanyak 42 (79,2%) responden. Hasil uji chi square menunjukan bahwa nilai p value 0,001 artinya ada Hubungan Caring Perawat Dengan Kepuasan Pasien. Terdapat hubungan caring perawat dengan kepuasan pasien di Ruang Rawat Inap RS. Diharapkan perawat dapat menerapkan perilaku caring perawat sehingga dapat mengoptimalkan pemberian asuhan keperawatan khususnya pada pasien rawat inap guna meningkatkan kepuasan pasien. Kata Kunci: Caring, Kepuasan, Perawat.